2009
DOI: 10.4049/jimmunol.0802046
|View full text |Cite
|
Sign up to set email alerts
|

Prednisolone Treatment Induces Tolerogenic Dendritic Cells and a Regulatory Milieu in Myasthenia Gravis Patients

Abstract: FOXP3-expressing naturally occurring CD4+CD25high T regulatory cells (Treg) are relevant in the control of autoimmunity, and a defect in this cell population has been observed in several human autoimmune diseases. We hypothesized that altered functions of peripheral Treg cells might play a role in the immunopathogenesis of myasthenia gravis, a T cell-dependent autoimmune disease characterized by the presence of pathogenic autoantibodies specific for the nicotinic acetylcholine receptor. We report in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 61 publications
4
42
1
4
Order By: Relevance
“…There are several agents [i.e., rapamycin, vitamin D analogues, granulocyte macrophage colonystimulating factor (GM-CSF); see below] that could be used to improve the function or enhance the numbers of Tregs [82,83]. In addition, a number of currently used immunomodulatory treatments for MG, including corticosteroids and IVIg [84][85][86], have been reported to induce an expansion of Tregs and/or an enhancement in Treg function. A fuller understanding of the mechanisms underlying these effects may be helpful in identifying novel treatment strategies.…”
Section: T-cell Signaling Pathways and Tregsmentioning
confidence: 99%
“…There are several agents [i.e., rapamycin, vitamin D analogues, granulocyte macrophage colonystimulating factor (GM-CSF); see below] that could be used to improve the function or enhance the numbers of Tregs [82,83]. In addition, a number of currently used immunomodulatory treatments for MG, including corticosteroids and IVIg [84][85][86], have been reported to induce an expansion of Tregs and/or an enhancement in Treg function. A fuller understanding of the mechanisms underlying these effects may be helpful in identifying novel treatment strategies.…”
Section: T-cell Signaling Pathways and Tregsmentioning
confidence: 99%
“…34 IDO is the high levels of IL-10, TGFβ, COX-2 and indoleamine-2,3-dioxygenase (IDO). 15 Others describe regDC as immature or semi-mature DC pretreated with IL-10, prednisolone or vitamin D3, [16][17][18][19][20] while some state that regDC are mature DC pretreated with TGFβ, 14 IL-10/TGFβ1 or IL-10/IL-6 ( Table 1). 21,22 Despite the present controversy in characterizing regDC, the role of DC with tolerogenic or immunosuppressive phenotypes in transplantation, allergy, autoimmune and infectious diseases has been repeatedly proven.…”
Section: Regulatory Dendritic Cellsmentioning
confidence: 99%
“…Data showed that this treatment can affect the production of Th1 or Th17 polarizing cytokines produced by innate immune cells, as well as T-cell capability to respond to these cytokines. 47,48 Furthermore, recent in vitro and in vivo studies showed that glucocorticoids can favor the establishment of pro-tolerogenic conditions. Human DCs treated with glucocorticoids up-regulate the GC-Induced Leucine Zipper protein (GILZ) and differentiate into tolerogenic cells capable of inducing IL-10-producing antigen-specific Tregs.…”
mentioning
confidence: 99%